2022
DOI: 10.3390/agriculture12091334
|View full text |Cite
|
Sign up to set email alerts
|

Contour Resampling-Based Garlic Clove Bud Orientation Recognition for High-Speed Precision Seeding

Abstract: Achieving fast and accurate recognition of garlic clove bud orientation is necessary for high-speed garlic seed righting operation and precision sowing. However, disturbances from actual field sowing conditions, such as garlic skin, vibration, and rapid movement of garlic seeds, can affect the accuracy of recognition. Meanwhile, garlic precision planters need to realize a recognition algorithm with low-delay calculation under the condition of limited computing power, which is a challenge for embedded computing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Contours of an image is resampled (13) to a specified number of points. It is done by removing any redundant dimensions from the contour.…”
Section: Details Of the Experiments • Contour Resamplingmentioning
confidence: 99%
“…Contours of an image is resampled (13) to a specified number of points. It is done by removing any redundant dimensions from the contour.…”
Section: Details Of the Experiments • Contour Resamplingmentioning
confidence: 99%
“…The first category has eleven papers under the following sub-heading: Intelligent sensing for the crop or machine system [1,4,7,9,10,12,16,17,22,23,26]. Currently, a large number of studies focus on deep learning techniques, which have shown their superb impact on robotic sensing applications, as reflected in this issue.…”
mentioning
confidence: 99%
“…Currently, a large number of studies focus on deep learning techniques, which have shown their superb impact on robotic sensing applications, as reflected in this issue. Some papers utilized improved YOLO-based [7,23,26], CNN-based [12,16] or RCNN-based [9] methods to developed a detection model for operating target recognition or performance evaluation from the RGB images. To achieve more accuracy, faster and compacter models may be popular due to the cost-effective and feasiblity with low-computing platforms.…”
mentioning
confidence: 99%